Infectious reproductive disease pathogens in dairy herd bulls. Issue 10 (October 2015) - Hancock, AS; Younis, PJ; Beggs, DS; Mansell, PD; Pyman, MF
<x xml:space="preserve">Abstract</x> Objective Investigate the presence of infectious reproductive disease pathogens in dairy herd bulls in south‐west Victoria, Australia, using a cross‐sectional study. Methods Dairy herd bulls from 32 herds were sampled for bovine viral diarrhoea virus (BVDV: 256 bulls, 32 herds) prior to the natural mating period, bovine herpes virus‐1 prior to (10 bulls, 5 herds) and after (118 bulls, 19 herds) the natural mating period, and for Campylobacter fetus spp. and Tritrichomonas foetus after the natural mating period (61 bulls, 7 herds). BVDV was detected from an ear‐notch sample using a commercially available rapid assay ELISA, bovine herpes virus‐1 and T. foetus were screened for by PCR from a penile swab and preputial sample respectively, and C. fetus spp. were screened for by culture of preputial samples. Results None of the bulls tested positive for BVDV antigen. Campylobacter fetus venerealis (or C. fetus fetus) was cultured in 6.6% (4/61) of bulls, representing 2 of the 7 (28.6%) farms that were not vaccinating bulls against bovine genital campylobacteriosis. Bovine herpes virus‐1 was identified in 7.8% (10/128) bulls sampled; T. foetus was not identified in any samples. Conclusion Bovine genital campylobacteriosis is present in south‐western Victoria, despite longstanding recommendations to vaccinate bulls. Screening bulls for persistent infection with BVDV is probably justified, despite the absence of persistently infected bulls in this study. Further research is warranted to investigate the potential reproductive implications of BHV‐1, and the presence of T. foetus.